Impact of Introduced Invasive Herbivores in Patagonian Forests - Barrios Garcia Moar, Maria Noelia (2023)
There are 13 invasive mammalian herbivore species in Argentina, which were introduced in the 15th and 19th centuries principally for livestock and hunting purposes. Currently, many of these invasive herbivores (e.g., cattle, Bos primigenius taurus; red deer, Cervus elaphus; wild boar, Sus scrofa; European hare, Lepus europaeus) have greatly expanded their distributions across Argentina, causing negative impacts to native biodiversity and ecosystem processes. Selective browsing or grazing by herbivores in Patagonian forests has been shown to decrease plant growth, increase mortality, and alter flowering season, seed set, and plant tissue chemistry of many herb, shrub and tree species. At the community level, invasive herbivores often heavily browse on just a few species, favoring browseresistant plants and thereby altering the species composition of native plant communities. Additionally, invasive herbivores can directly impact native herbivores through competition for resources and habitat modifications. Competition for food, for example, is likely to affect native herbivores like the Patagonian huemul (Hippocamelus bisulcus), guanaco (Lama guanicoe), and southern pudu (Pudu puda), given their diet overlap. Additionally, several studies have shown that invasive herbivores can alter entire food webs by increasing food availability for native predators or by disrupting plant-animal mutualisms that lead to trophic cascades. Lastly, invasive herbivores can also cause ecosystem level impacts by altering nutrient cycling, hydrology, and disturbance regimes. Notably, wild boar rooting and North American beaver (Castor canadensis) dam construction can cause long-lasting impacts to native ecosystem structure and function. While there is a relatively good understanding of introduced invasive herbivore impacts in Patagonian forests, there is still a need for more study of their impacts in other biomes and in relation to co-occurring invasive species. There is also a particular need, as with most introduced invasive species, to focus greater attention on how to manage this socio-ecological problem.